Normal Laws for Two Entropy Estimators on Infinite Alphabets - Chen, Chen (Entropy (Basel), 2018)
This paper offers sufficient conditions for the Miller–Madow estimator and the jackknife estimator of entropy to have respective asymptotic normalities on countably infinite alphabets.